A Proposed Vision For Managing Tourist Ambulance Services In Light Of Enriching The Visitor Experience And Achieving The Goals Of Vision 2030 (The Review of Diabetic Studies, 2025)
Background:Tourism represents a major pillar of Saudi Arabia’s Vision 2030, which seeks to diversify the national economy and enrich the visitor experience through high-quality, safe, and sustainable services. Within this vision, emergency medical preparedness—particularly tourist ambulance services—plays a critical role in ensuring visitor safety and satisfaction while strengthening the Kingdom’s international reputation.Objective:This systematic review proposes an integrated vision for managing tourist ambulance services that aligns prehospital emergency care with visitor-experience goals and national transformation initiatives under Vision 2030.Methods:Following the PRISMA 2020 guidelines, relevant publications (2019–2025) were systematically identified across PubMed, Scopus, Web of Science, and major academic publishers. Sources included books, peer-reviewed studies, and official Saudi policy documents addressing emergency medical systems (EMS), mass-gathering medicine, and visitor-experience design. Thematic synthesis generated three overarching domains: system governance, experience-centered service design, and policy alignment with Vision 2030.Results:Twenty-two eligible sources highlighted that effective tourist ambulance services require integrated governance among the Ministry of Health, Saudi Red Crescent Authority, and Ministry of Tourism; digital interoperability; culturally competent workforce training; and continuous quality monitoring.Conclusion:The proposed Tourist Ambulance Vision Framework (TAVF) outlines a multidisciplinary roadmap combining clinical excellence, empathy-driven service delivery, and smart-technology integration. Implementing this framework can transform ambulance encounters into positive, reassuring experiences that advance Saudi Arabia’s Vision 2030 objectives of safety, hospitality, and sustainable tourism growth.